Analysis of History Materials of Teaching Book History of Islamic Culture in Islamic Senior High School - daud, safari (Universitas Islam Negeri Raden Intan Lampung, 2018)
AbstractConceptually, Islam history with its special historiography characteristic has got scientific recognition that is not only in Islamic side. In the context of history of Islamic culture, it has implication relates to an effort for harmonizing between historical material with some lessons or morar value to become a basis for morality to then turn into the soft-skill development. Thus, several things relate to the exposure and the understanding of Islamic history at school, need to be stated in detail to become the subject for further research. The interesting thing to learn is the fulfillment of historical needs regarding chronological aspects and historical material testing according to some criteria that apply in historical research methodology. This research belongs to the category of library research. In this case , research data sources, both those directly or indirectly related to written material published in textbooks do not meet the standards of scientific work. The easiest indicator to see is the absence of footnotes, interpretations and looks only moving from the reference book. again, this is related to the motive for the preparation of textbooks arrangements which are intended for purely educational purposes regardless to material validity to then turn to conclusion that the history textbook of Islamic culture is very difficult to be called as a history book, in the level of books and historical literature, it is in the tertiary position.Keywords : Analysis, Islamic Senior High School, History of Islamic culture